Child Judicial System: Islamic Criminal Law Concerning Criminal Enforcement of Children in The Court of Subang District - Tuti Herawati (LEGAL BRIEF, 2021)
The development of communication technology is one of the causes of the increase in the crime rate in children so that they are caught in criminal acts. Regarding this matter, the Indonesian government has compiled a law on juvenile justice and implemented restorative justice. Likewise with Islamic law, which regulates punishment for children. This study uses a narrative method with a qualitative approach. The purpose of this research is to find out how child crime is enforced in the justice system. The results of this study indicate that the enforcement of juvenile crime can be attempted to use diversion, but still see what cases the children do first. Not all juvenile criminal cases can be resolved by means of diversion justice.